PELAKSANAAN REBOISASI SEBAGAI PENCEGAH LONGSOR LAHAN MIRING DI DESA BAOSAN LOR KECAMATAN NGRAYUN PONOROGO - Intan Noor , Salsabila; Ernawati, Ernawati; Ike Nurhayati, Marianti; Najih, Ainun; Rizky Adianto, Muhammad; Musarofah, Siti (Journal of Islamic Science Community, 2023)
Indonesia in the rainy season every year, is often hit by landslides. The main cause of the landslide disaster is due to high rainfall, but the soil cannot accommodate the rainwater. So that Institut Aagama Islam Riyadlotul Mujahidin Students participating in KKN held reforestation activities to prevent landslides on sloping land with the assistance of the Village Government and the surrounding community. This dedication activity aims as education on preventing the threat of landslides by app lying a reforestation activities to the Baosan Lor village area. Activities are carried out by providing instructions regarding good and correct reforestation techniques. The output of this dedication the development of the Baosan Lor community’s insights on the threat of landslides in the area of residence and conservation efforts independently by the community using a reforestation activities.